Strategy System and Information Technology Planning In PT.Trikarsa Sempurna Sistemindo - Muhamad Abdul Holik (Bina Nusantara University, 2015)
This research is to provide strategic design of information systems/information technology to the PT. Trikarsa Sempurna Sistemindo. With the design of information systems strategy, it is expected that within the next four years (2012-2015) business developments of PT TSS can be supported appropriately by the system and information technology that has been invested in PT TSS. Data in this research is collected through discussion, study and questionnaires. The collected data is then processed using the methodology of Ward and Peppard and supporting tools that generate qualitative analysis of information. From the analysis, it can be concluded that in order to make the achievement of a good business then PT TSS should do three thing. First, improve work efficiency by automating various processes of information management. Second, improve management effectiveness by satisfying the information needs for decision making. Third, improve or enhance the competitiveness of the organization by changing styles and ways of doing business.